Prevalence and individual factors associated with unsuppressed viral load among HIV patients receiving antiretroviral therapy at Ndejje Health Centre IV, Wakiso district. A cross-sectional study. - Ssemanda , Ali; Miiro, Richard; Nansereko, Hasifah; Ssemuwemba, Franscisco; Nalubega, Jane Frank; Naggulu, Immaculate Prosperia (Student's Journal of Health Research Africa, 2026)
Background: Unsuppressed HIV viral load remains a major public health challenge among people living with HIV receiving antiretroviral therapy (ART), particularly in low- and middle-income countries. This study assessed the prevalence and individual factors associated with unsuppressed viral load among HIV patients receiving ART at Ndejje Health Centre IV, Wakiso District. Methodology: A descriptive cross-sectional study was conducted among 77 HIV-positive adults aged 18 years and above who had been on ART for at least six months. Participants were selected using purposive sampling. Data were collected using semi-structured questionnaires and supplemented with clinical records for viral load results. Data were analyzed using descriptive statistics, including frequencies and percentages. Results: Most participants were aged 25–34 years (36.4%) and female (57.1%). The prevalence of unsuppressed viral load was 33.8% (26/77), while 66.2% (51/77) had suppressed viral loads. The majority had primary education (36.4%) and were unemployed (40.3%). Most respondents reported having family or social support for HIV treatment (66.2%), while 29.9% experienced stigma or discrimination. Individual factors, such as unemployment, lower educational level, and limited social support, were identified as potential contributors to unsuppressed viral load. Conclusion: The prevalence of unsuppressed viral load among patients receiving ART at Ndejje Health Centre IV was relatively high, indicating ongoing challenges in achieving optimal treatment outcomes. Socioeconomic factors, education level, and social support appear to influence viral suppression among patients on ART. Recommendations: Healthcare providers should strengthen adherence counseling, particularly for patients who are socioeconomically vulnerable. The Ministry of Health and partners should integrate economic empowerment programs and community support interventions to improve adherence and retention in care. Routine viral load monitoring and stigma reduction strategies should also be enhanced to improve treatment outcomes.